2022
DOI: 10.3389/fpubh.2022.792164
|View full text |Cite
|
Sign up to set email alerts
|

Does Mothers' Awareness of Health and Nutrition Matter? A Case Study of Child Malnutrition in Marginalized Rural Community of Punjab, Pakistan

Abstract: Maternal nutritional awareness might reduce the risk of malnutrition in children. This study assesses the impact of mothers' nutritional and health awareness (MNHA) on the nutritional status of pre-school children in rural South Punjab. Using a proportionate purposive simple random sampling technique we collect data with the help of a self-administered questionnaire on height, age, the weight of children, and socio-economic profile from 384 rural households in one of the marginalized districts of Punjab. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Not aligned well with local socio-cultural realities, the short-term global technical solution in the form of RUTFs and CMAM was implemented "under neoliberal governments and facilitated an increasingly inequitable economy with minimal state involvement in an increasingly individualistic social environment" [54] (p. 16). However, the permanent, long-term, sustainable solution to maternal child undernutrition lies in females' socioeconomic emancipation, and their health or nutrition literacy [55][56][57][58][59]. In addition, the inclusion of training of medical staff on respectful care is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Not aligned well with local socio-cultural realities, the short-term global technical solution in the form of RUTFs and CMAM was implemented "under neoliberal governments and facilitated an increasingly inequitable economy with minimal state involvement in an increasingly individualistic social environment" [54] (p. 16). However, the permanent, long-term, sustainable solution to maternal child undernutrition lies in females' socioeconomic emancipation, and their health or nutrition literacy [55][56][57][58][59]. In addition, the inclusion of training of medical staff on respectful care is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also testified of the inappropriate counseling skills during pregnancy. In addition, the immediate post-delivery period at the maternity homes and hospitals ( 24 , 25 ) remains a serious public health concern. Inappropriate counseling is often linked to various types of misconceptions and social disbeliefs that prevail ubiquitously across sectors.…”
Section: Discussionmentioning
confidence: 99%
“…In Rahim Yar Khan District, underweight prevalence rates are 46.1%, whereas stunting and wasting prevalence rates are 34.83% and 15.49%, respectively. Around 83.17% (430) of respondents have above 5 km distance to the nearest healthcare facility, 8.32% (43) of respondents have a 3 to 4 km distance, and 8.51% (44) have a distance less than or equal to 2 km from the nearest healthcare center. Around 75.82% (392) of respondents reported that LHWs have not visited their houses in the last 15 days, while 24.18% (125) reported that they have visited (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that amongst the richer and richest families, the prevalence of malnutrition was the lowest [40,41]. Some recent studies from the same region also show that household socioeconomic deprivation (HDS) strongly contributed to child malnutrition, and malnutrition decreased with a decrease in deprivation status [42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%